A social entrepreneurship case study of the “Pertubuhan Kebajikan Anak Yatim Islam Segamat” orphanage in Malaysia/ Saunah Zainon...[et al.] - Zainon, Saunah; Ismail, Rina Fadhilah; Soo, Kum Yoke; Ahmad, Haryati; Sa’udah @ Suhadak, Nurulzulaiha (UiTM Cawangan Johor, 2019)
Most orphanages in Malaysia are run by means of charitable donations. However, the donations and contributions collected are usually not regular or one-off. This has led to orphanages being in a run-down state and ill-equipped. The care given to orphans is important as part and parcel of their human rights to be treated and given a fair chance of living with the rest of the human race. As such, this paper aims to investigate the role of social entrepreneurship in providing care for orphans. Particularly, the paper will focus on an orphanage – “Pertubuhan Kebajikan Anak Yatim Islam Segamat” (PKAYIS) which is locatedin the state of Johor. PKAYIS has provided shelter for 68 orphans and through charitable donations has been running successfully since 1983. The orphanage has been able to successfully bring up orphans who have succeeded academically and found successful careers in life. Based on the theoretical framework on social entrepreneurship and orphans, observation methods and interviews were carried out to supply relevant information and data for the study. This paper will provide some insights on how social entrepreneurship affects the society and would be beneficial for policy makers interested in adopting social entrepreneurship as a mean of care for orphans.